The Effectiveness of Spiritual Therapy on Cognitive Emotion Regulation and Life Satisfaction in Individuals With Type 2 Diabetes - Mahrokh Javaherforooshzadeh; Parvin Ehteshamzadeh; Farzaneh Hooman; Saeed Bakhtiarpour (Health, Spirituality and Medical Ethics)
Background and Objectives: Type 2 diabetes is a chronic condition that can significantly impact emotional well-being. Individuals often struggle with emotional regulation, leading to decreased life satisfaction. Therefore, this study aimed to determine the effect of spiritual therapy on cognitive emotion regulation (CER) and life satisfaction in individuals with type 2 diabetes. Methods: This study employed a quasi-experimental design utilizing a pre-test and post-test approach with a control group. The target population encompassed all individuals diagnosed with type 2 diabetes working within the Mashhad education sector in 2023. A convenience sampling method was employed to recruit a sample of 24 participants (equally divided into two groups) who met the study’s inclusion criteria. Random assignment allocated participants to either the experimental or control group. Both groups completed the CER questionnaire and the satisfaction with life scale at both the pre-test and post-test stages. The experimental group received spiritual therapy delivered in eight sessions, each lasting 90 minutes. Data analysis was conducted using analysis of covariance (ANCOVA). Results: The findings revealed a significant reduction in maladaptive CER scores in the post-test stage for the group receiving spiritual therapy compared to the control group (P<0.001). The results also showed that spiritual therapy led to an increase in adaptive CER and life satisfaction at post-test (P<0.001). Conclusion: The findings demonstrated that spiritual therapy yielded significant benefits for the intervention group. These results suggest that spiritual therapy can be a valuable complementary approach for managing emotional challenges and improving overall well-being in individuals with type 2 diabetes.